High Positivity Yield of HIV Index Case Testing in Mamfe Health District, South West Region, Cameroon - Julius, Mekolle, Enongene; Edouard, Tshimwanga, Katayi; Asongwe, Mboh, Khan, Eveline; Bedifeh, Benard, Atembeh; Boeyeo, Forsi; Chuyum, Aseh, Christian (My University, 2022)
Background: Index testing (IT) is a voluntary process whereby after obtaining consent, sexual partners of HIV seropositive clients are offered HIV testing services. IT has been associated with high HIV positivity. The aim of this study is to determine the positivity rate and factors influencing IT yield among sexual partners (SP) of newly diagnosed Index clients (IC) at Mamfe Health District, Cameroon. Methods: At Mamfe District Hospital, the main district HIV care and treatment center, records of all newly diagnosed HIV positive clients with an outcome for IT between July and September 2021, were reviewed retrospectively. Data including age and gender of the IC and their partners, method of referral and notification of partners, HIV test results of partners and linkage status of new HIV positive partners were collected using a chart abstraction template from the IT registers. Analyses were done using the R Software Package version 4.0.4. Chi-square was used to test association between different groups at a significance level of p<0.01. Results: Records of 133 consecutive newly diagnosed IC, 48.1% males vs 51.9% females and their 156 listed SP, 50.6% males vs 49.4% females were reviewed. Mean ages of IC and SP were 39±10 and 37±11 years respectively and a majority of IC (39.9%) and SP (42.9%) were in the 35-44 years age group. 37.2% (58/156) of partners tested positive for HIV and were all linked to antiretroviral therapy. All SP were notified using provider referral method. HIV results of both male and female partners were not significantly associated with age group (p>0.05). HIV positivity rate of 42.9% (33/77) in female partners was not significantly higher than 31.6% (25/79) in male partners (p>0.05) Conclusions: The positivity rate of IT among the SP of new IC was high with no significance in gender difference. Most of the IC and SP were aged 35-44 years and essentially in heterosexual relationships. Prioritizing and sustaining IT to partners of new IC using provider referral is a veritable strategy and need to be implemented with fidelity to increase case finding in order to boost ART uptake, especially in the 35-44 years age group.
Keywords: Cameroon; Case identification; Index testing; Sub-Saharan Africa